1) у = х-7
2) у = -2х-1
1) (0; -7), (1; -6), (-1; -8), (2; -5)
2) (0; -1), (1; -3), (-1; 1), (2; -5;)
Мы в восьмом по таблице делаем. Изменяем х в обе стороны (- и +), начиная с нуля. х=0, х=1, х=-1, х=2. Когда у1 = у2, находится общая точка.
ответ: (2; -5).
1) у = х-7
2) у = -2х-1
1) (0; -7), (1; -6), (-1; -8), (2; -5)
2) (0; -1), (1; -3), (-1; 1), (2; -5;)
Мы в восьмом по таблице делаем. Изменяем х в обе стороны (- и +), начиная с нуля. х=0, х=1, х=-1, х=2. Когда у1 = у2, находится общая точка.
ответ: (2; -5).